Singapore Management University Report to Stakeholders 2001 - 2002 - Singapore Management University (Institutional Knowledge at Singapore Management University, 2001)
If the first year of incorporation was the paving of the foundation for SMU, the second year was one of laying the first building blocks. For the university, this was a year for surging ahead – of exploration and adventure. With a sizeable student population, a faculty of international repute and two schools going on three, SMU is growing from strength to strength at an unbelievable rate. But beyond sheer numbers, I sense and see a spirit of fervour and adventure in the work of students, faculty and staff in every corner of this institution that we have founded. Our students have beaten the odds to win international business competitions and shown their mettle in all areas ranging from sports to culture to community activities. They display a thirst for challenging the unquestioned, for conquering the unknown. This is the very same spirit that the Singapore government has been striving to nurture – that which is believed to spur entrepreneurship, the passion for enterprise and the eagerness to make things happen.